Plant Signaling Molecules : role and regulation under stressful environments - Khan, M. Iqbal R.; Reddy, Palakolanu Sudhakar; Ferrante, Antonio; Khan, Nafees A. (Woodhead Publishing, 2019)
Plant Signaling Molecule: Role and Regulation under Stressful Environments explores tolerance mechanisms mediated by signaling molecules in plants for achieving sustainability under changing environmental conditions. Including a wide range of potential molecules, from primary to secondary metabolites, the book presents the status and future prospects of the role and regulation of signaling molecules at physiological, biochemical, molecular and structural level under abiotic stress tolerance. This book is designed to enhance the mechanistic understanding of signaling molecules and will be an important resource for plant biologists in developing stress tolerant crops to achieve sustainability under changing environmental conditions.